2015
DOI: 10.1038/onc.2015.63
|View full text |Cite
|
Sign up to set email alerts
|

PML isoforms IV and V contribute to adenovirus-mediated oncogenic transformation by functionally inhibiting the tumor-suppressor p53

Abstract: Although modulation of the cellular tumor-suppressor p53 is considered to have the major role in E1A/E1B-55K-mediated tumorigenesis, other promyelocytic leukemia nuclear body (PML-NB)/PML oncogenic domain (POD)-associated factors including SUMO, Mre11, Daxx, as well as the integrity of these nuclear bodies contribute to the transformation process. However, the biochemical consequences and oncogenic alterations of PML-associated E1B-55K by SUMO-dependent PML-IV and PML-V interaction have so far remained elusive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 132 publications
(167 reference statements)
2
21
0
Order By: Relevance
“…Studies from Pennella and coworkers suggest that E1B-55K is also a p53-SUMO1 E3 ligase (63). In line with this, we recently showed that E1B-55K SUMOylation and, hence, PML-NB localization are prerequisites for the SUMO ligase activity of the viral protein (31). However, the detailed mechanism of how E1B-55K mediates the SUMOylation of other proteins is still not fully understood.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Studies from Pennella and coworkers suggest that E1B-55K is also a p53-SUMO1 E3 ligase (63). In line with this, we recently showed that E1B-55K SUMOylation and, hence, PML-NB localization are prerequisites for the SUMO ligase activity of the viral protein (31). However, the detailed mechanism of how E1B-55K mediates the SUMOylation of other proteins is still not fully understood.…”
Section: Discussionsupporting
confidence: 50%
“…KAP1 point mutations were introduced by site-directed mutagenesis using the primers shown in Table 1. For transient transfection, subconfluent cells were treated with a transfection mixture of DNA and 25-kDa linear polyethylenimine as described recently (31).…”
Section: Methodsmentioning
confidence: 99%
“…Despite being one of the least abundant isoforms, PMLIV has been the most intensively studied PML isoform so far, gaining attention because of its ability to mediate p53‐induced senescence and apoptosis (Bernardi, Papa, & Pandolfi, ; Wimmer et al, ). Numerous studies have identified that PMLIV ‐induced senescence involves stabilization and activation of p53 through phosphorylation at Ser 46 and acetylation at Lys 382 (Ivanschitz et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Scale bar = 20 μm. co-IP, coimmunoprecipitation; DAPI, 4,6-diamidino-2-phenylindole; GADPH, glyceraldehyde 3-phosphate dehydrogenase; ns, not significant; MCF-7, Michigan Cancer Foundation-7; PML, promyelocytic leukemia; TGF-β1, transforming growth factor-β1 [Color figure can be viewed at wileyonlinelibrary.com] because of its ability to mediate p53-induced senescence and apoptosis (Bernardi, Papa, & Pandolfi, 2008;Wimmer et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Since E1B-55K, in conjunction with E4orf6, mediates ubiquitinylation and proteasomal degradation of p53, this was the first example of a viral protein having dual activity in both the ubiquitin and SUMO pathways. Mutation of the p53 sumoylation site decreased the ability of E1B-55K to repress the transcriptional activity of p53 and to tether p53 in PML bodies (Pennella et al 2010;Wimmer et al 2016). These results demonstrate that the E1B-55K protein induced sumoylation is functionally relevant and contributes to the overall abrogation of p53 defenses in the adenoviral infected cell.…”
Section: Adenovirusesmentioning
confidence: 99%